SUSTAINABILITY REPORTING AND TAX AGGRESSIVENESS BEFORE AND DURING COVID-19: GCG MODERATING VARIABLE - Triwacananingrum, Wijaya; Wijaya, Gabriella Michelle (Jurnal Akuntansi dan Keuangan Indonesia, 2022)
This research aimed to examine the incremental effect of COVID-19 on sustainability reports disclosures towards tax aggressiveness by moderating Good Corporate Governance (GCG) in a balanced period before and during COVID-19. Disclosure of sustainability reports and tax aggressiveness are measured using the GRI Standards index and the Effective Tax Rate (ETR), respectively. Meanwhile, GCG is measured based on 15 indices (ICGI) developed by Tanjung (2020). An analytical method in the form of multiple linear regression was used on 100 companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2020 as the research object. The results did not show significance in proving the incremental effect of COVID-19 on the variables tested. Additional testing was carried out with a split per year, which showed that before COVID-19, sustainability reports disclosures did not affect tax aggressiveness, as opposed to during its occurrence. Before COVID-19, GCG weakened the negative relationship between disclosure of sustainability reports and tax aggressiveness. Meanwhile, during COVID-19, it had a lower level of weakening the negative relationship between the two.